Hybrid repair of type A aortic dissection after infrarenal endovascular aortic repair and bilateral iliac branched grafts - Quynh-Anh L. Dang, BS, BBA; Ciaran S. O'Brien, MD; William Rothstein, MD; Chase Brown, MD; Venkat Kalapatapu, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Type A dissection is infrequently reported after infrarenal endovascular aortic repair (EVAR). Here, we present a case of an EVAR with iliac branch endoprosthesis complicated by type A dissection requiring ascending arch repair. After hemiarch repair, the patient was noted to have residual type B dissection, malperfusion of the left renal artery, and compression of the EVAR with left external iliac limb occlusion. These were treated successfully with iliac thrombectomy and dissection stent placement.